The Contribution of Savings and Loan Cooperatives to Financial Inclusion in Indonesia - Zainudin, Ellyza; Setiawan, Fajar Ari; Napitupulu, Diana Ria Winanti (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Savings and Loan Cooperatives in Indonesia have a very important role in increasing financial inclusion, especially among low-income communities and groups that are not reached by conventional banking services.Purposes of the Research: Analyze the contribution of Savings and Loan Cooperatives to financial inclusion in Indonesia, identify the challenges faced, and provide recommendations to improve the role of cooperatives in expanding financial access for the community.Methods of the Research: This study uses a qualitative approach with descriptive analysis to describe the role and contribution of Savings and Loan Cooperatives to financial inclusion in Indonesia.Findings of the Research: This research shows that Savings and Loan Cooperatives have great potential in reducing inequality of access to finance, but also need improvements in terms of regulation, technology, and financial education to be more effective in achieving their goals. Savings and Loan Cooperatives in Indonesia have a very important role in increasing financial inclusion, especially among low-income communities and groups that are not reached by conventional banking services. This paper analyzes the contribution of Savings and Loan Cooperatives to financial inclusion in Indonesia, identifies the challenges faced, and provides recommendations to improve the role of cooperatives in expanding financial access for the community. This research shows that Savings and Loan Cooperatives have great potential in reducing inequality of access to finance, but also need improvements in terms of regulation, technology, and financial education to be more effective in achieving their goals.